PENGARUH PENYULUHAN TENTANG EKSTERNAL DOUCHING VAGINA TERHADAP PENGETAHUAN DAN SIKAP REMAJA - Debbiyatus Sofia (Oksitosin : Jurnal Ilmiah Kebidanan, 2016)
External vaginal douching is cleaning the outside of the vagina activity with certain materials. Activities outside of the vagina cleans indiscretion can worsen the condition of the vagina, but it also can increase the risk of sexually transmitted infections (STIs), inflammation of the vulva to inflammation of the vagina. This study aimed to determine the effect of external counseling about vaginal douching on knowledge and attitudes of teenagers. Design of this research is pre experimental design "one group pretest-posttest design". Population of all students in the dorm Tahfidzul Quran daughter as much as 77 students. Sampling methods using simple random sampling with 69 respondents, the research instrument using checklists. Data were analyzed using Wilcoxon Signed Rank test with the highest value of α = 0:05. Wilcoxon Signed Rank test results, the respondents' knowledge Z arithmetic = -6488> Ztable = 1.96, then H0 was rejected, which means no external influence on the extension of the knowledge of vaginal douching adolescent female students before and after a given extension. And attitudes of students known Z arithmetic = -4642> Ztablel = 1.96, then H0 was rejected, which means no external influence of illumination on the vaginal douching adolescent attitude towards women students before and after a given extension. Keyword: Counseling, Knowledge, Attitude, External Douching Vaginal ABSTRAK Eksternal douching vagina merupakan kegiatan membersihkan vagina bagian luar dengan bahan–bahan tertentu. Kegiatan membersihkan vagina bagian luar yang kurang bijaksana dapat memperburuk kondisi vagina, selain itu juga dapat meningkatkan resiko Infeksi Menular Seksual (IMS), Penelitian ini bertujuan untuk mengetahui pengaruh penyuluhan tentang eksternal douching vagina terhadap pengetahuan dan sikap remaja. Desain dalam penelitian ini adalah pre eksperimental dengan rancangan “One Group Pretest-Posttest Design”. Populasi seluruh santri di asrama Tahfidzul Qur’an putri sebanyak 77 santri. Metode sampling menggunakan simple random sampling dengan jumlah responden 69, instrument penelitian menggunakan checklist. Analisa data menggunakan Ranking Bertanda Wilcoxon Hasil uji Ranking Bertanda Wilcoxon, pada pengetahuan responden Zhitung = -6.488 > Ztabel = 1.96, maka H0 ditolak yang artinya ada pengaruh penyuluhan tentang eksternal douching vagina terhadap pengetahuan remaja santri putri sebelum dan setelah diberi penyuluhan. Dan sikap santri diketahui Zhitung = -4.642 > Ztabel = 1.96, maka H0 ditolak yang artinya ada pengaruh penyuluhan tentang eksternal douching vagina terhadap sikap remaja santri putri sebelum dan setelah diberi penyuluhan. Kata Kunci : Penyuluhan, Pengetahuan, Sikap, Eksternal Douching Vagina